Organizational behavior - McShane, Steven Lattimore (McGraw-Hill Irwin, 2005)
In their substantially revised Third Edition, McShane and Von Glinow continue the trailblazing innovations that made previous editions of Organizational Behavior recognized and adopted by the new generation of organizational behavior (OB) instructors. Acclaimed for its readability and presentation of current knowledge, this textbook's philosophy is that OB knowledge is for everyone, not just traditional managers. The new reality is that everyone -- sales representatives, production employees, physicians -- needs OB knowledge to successfully work in and around organizations. Organizational Behavior, 3rd Edition, is unparalleled in its ability to engage students by bringing cutting edge OB concepts closer to reality through the 'theory-practice link' approach. McShane and Von Glinow help readers connect OB theories to emerging workplace realities through hundreds of fascinating real-life stories from across the United States and around the world. McShane/Von Glinow's Organizational Behavior 3rd Edition also continues to be the source of the hottest topics, such as: workaholism, virtual teams, corporate social responsibility, Schwartz's values model, innate drives theory, workplace emotions, executive coaching, guanxi, appreciative inquiry, social identity theory, workplace bullying, workplace justice, and much, much, more